GASTRO ESOPHAGEAL REFLUX DISEASES IN CHRONIC OBSTRUCTIVE PULMONARY DISEASE PATIENTS - Khan, Hamid Nisar; Suleman, Amir; Ullah, Raza; Abdullah, Azmat; Naz, Shahida (Journal of Ayub Medical College Abbottabad, 2017)
Background: There is an association of Gastroesophageal reflux disease (GERD) with chronic obstructive pulmonary disease (COPD). This study was designed to determine the frequency of GERD in COPD patients. Methods: This descriptive, cross-sectional study was conducted in the Pulmonology Unit Ayub Teaching Hospital Abbottabad. Patients more than 40 years of age of both genders presenting with features of COPD such as cough and breathlessness for more than 6 months and confirmed by spirometry were included in the study. A total of 118 consecutive patients were included in the study. Patients who had spirometry showing FEV1 <70% predicted & FEV1/FVC ratio <70% were included. Patients of asthma, with known oesophageal disease such as cancer, stricture, achalasia or active peptic ulcer disease, Pregnancy (precipitates GERD) and those patients who had used proton pump inhibitors (PPI) in the last 15 days were excluded. Results: The mean age of COPD patients was 65.25 years. Among COPD patients 89 (75.4%) were males. Fifty-five (46.6%) patients had moderate COPD (FEV1:50-69%). Frequency of smokers was 68.6% with mean duration of 12.5years and mean number of cigarettes smoke per day were 13.4. Thirty-five (29.75%) had GERD; 27% in males and 30% in females. Conclusion: Our study shows that a higher proportion of gastro oesophageal reflux (GERD) symptoms are present in COPD patients and it also shows that GERD is more common in severe COPD patients. Keywords: Gastroesophageal reflux disease, GERD; chronic obstructive pulmonary disease; COPD; spirometry; Proton Pump Inhibitors